Gabon : Selected Issues and Statistical Appendix. (IMF Staff Country Reports; Country Report ;, 2005)
This Selected Issues and Statistical Appendix paper on Gabon reviews management of oil revenues, competitiveness, and growth. The nature of Gabon's problems has not changed during the past 15 years. The need to diversify the economy and the export base; control fiscal expenditure and the wage bill; carefully assess capital expenditure; and reform public sector enterprises are the challenges that the Gabonese need to be prepared to implement adequately. Gabon faces huge medium-term fiscal constraints imposed by the expected steady decline in oil production and its depletion.